The Influence of Entrepreneurial Experience on Cognitive Biases (Illusion of Control and Belief in the Law of Small Numbers) in Decision Making Process - The Chit,Phay; Leong,Yan Ci (2025)
Entrepreneurs often face the need to make quick decisions under uncertainty. To cope with this pressure, they may develop cognitive biases such as the illusion of control, where they overestimate their influence over outcomes, and the belief in the law of small numbers, where they rely on limited information to draw conclusions. While these biases are highly relevant in entrepreneurship, there is limited research exploring the determinants of the biases. This thesis explores the following research question: How does entrepreneurial experience shape the manifestation of the illusion of control and the belief in the law of small numbers in entrepreneurial decision-making? We conducted semi-structured interviews with ten entrepreneurs from diverse industries and backgrounds, using the Gioia methodology to identify emerging themes through first- and second-order coding. Our findings suggest that experience does not directly enhance or mitigate the presence of these biases. Instead, experience influences how these biases emerge through several mechanisms. First, cognitive lenses shaped by prior education and work experience affect how entrepreneurs interpret information, perceive control, and respond to uncertainty. Second, decision-making patterns evolve with experience—entrepreneurs become more comfortable with making quick decisions, more confident in trusting their intuition, better at sourcing relevant information and assessing opportunities. Third, experience informs the way entrepreneurs frame action in context. They learn the importance of timely decisions and become more deliberate in managing relationships as their market position strengthens. Overall, this study contributes a clearer understanding of how experience shapes bias, offering a more nuanced foundation for future research and practice. We propose that future research should consider combining qualitative approaches with quantitative or longitudinal designs to further test and build on the insights of this study. We also propose future work could explore a broader set of cognitive biases and examine how they interact with entrepreneurial experience.
Keywords: Entrepreneurial Experience; Entrepreneurial Decision Making; Cognitive Bias; Illusion of Control; Belief in the Law of Small Numbers; Cognitive Mechanisms